EFEKTIVITAS PENGELOLAAN IRIGASI DENGAN SUMUR POMPA GUNA MENINGKATKAN POLA TANAM DI KECAMATAN NEGARA, KABUPATEN JEMBRANA - Putra Wiryawan, Agus Gede; Norken, I N; Purbawijaya, IBN (JURNAL SPEKTRAN; Vol 4 No 1 (2016): Vol. 4, No. 1, Januari 2016DO - 10.24843/SPEKTRAN.2016.v04.i01.p09)
Abstrac k : Jembrana Regency especially Negara District have two river caracteristics such as the river which located in western Melaya River only flow when the rainy season and the rivers located between western Klatakan river and eastern Pulukan river flow every years with low discharge. it caused failing of harvest. So the ground water used to supply the surface water needs. But, complaint comes from the farmer caused by the expensive cost of operational generating set. The approach doing by study and research directly to the well pump which located in Negara district. Purposive sampling used  to determine the respondents in this quisionaires. Likert scale used to measure attitudes, opinon and perceptions from the respondents on data analyzed by descriptive qualitative. The research showed resource, subak organization, operational and maintenance generating set, pump, and financial. Work on 82% reaching effectiveness of irrigation management with pump well in Negara district. And, based on result of double linier regression simultaneous and partial, showed that the significant effect to effectiveness of irrigation management with pump well in Negara district, Jembrana regency.
Keywords: effectiveness irrigation management, pump well, system planting pattern